The Contribution Of Flexibility To Badminton Smash Skills At SMP Negeri 6 Seluma - Febriansyah Adi Putra; Citra Dewi; Dwingki Marta Putra (Journal of Education, 2026)
This study aims to determine the contribution of flexibility to badminton smash skills at SMP Negeri 6 Seluma. This research method is Correlation research. The research sample amounted to 20 people. The instrument used in this study was a test of flexibility and badminton smash skills. Where the results of the study on flexibility to badminton smash skills at SMP Negeri 6 Seluma have a contribution of 90.80% which means that the flexibility test can be used as a measuring tool to improve badminton smash skills at SMP Negeri 6 Seluma.